REE patterns as a tool for recognition of diagenetic beds: a case from the Lower Devonian Upper Gaspé Limestones, Gaspé Peninsula, Québec - Lavoie, Denis; Bergeron, Mario (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 1993)
Analyses of rare earth elements (REE), major elements, insoluble residue content and mineralogy were performed on carbonate and siliciclastic samples from the Early Devonian Upper Gasp£ Limestones in eastern Gaspd Peninsula. Siliciclastic rocks are richer in REE than coeval mechanically deposited carbonates. A positive relationship between the absolute amount of REE and the content of aluminosilicate is clear for most samples. Even if poor in aluminosilicate, diagenetic carbonate concretions are the richest in REE. The concretions also show a significant negative Europium anomaly. Mineralogical, major element and stable isotope data show that calcite cementation resulting in the concretions was rapid and completed before reaching the methanogenic zone. Diagenetic conditions were responsible for remobilization of the REE from host detrital material and for raising the REE content of the concretions. The REE pattern is a potential tool for recognition of diagenetic beds produced in various geochemical environments.